Utility and Clinical Application of Circulating Tumor DNA (ctDNA) in Advanced Prostate Cancer - Louise Kostos; Heidi Fettke; Edmond M. Kwan; Arun A. Azad (Société Internationale d’Urologie Journal)
The treatment landscape for metastatic prostate cancer has undergone significant changes in recent years. The availability of next-generation imaging techniques and the emergence of novel therapies have led to earlier and more aggressive treatment approaches for patients. However, despite these advancements, drug resistance and progression to castration-resistant disease remain inevitable. Understanding the molecular landscape of advanced prostate cancer lies at the forefront of being able to deliver personalized therapies and more robustly risk-stratify patients, when combined with clinical factors. Advanced prostate cancer is characterized by inter- and intratumoral heterogeneity, posing challenges in comprehensively analyzing the genomic tumor profile using a solitary tissue sample. Additionally, the disease often manifests as bone-predominant metastatic tumors, making biopsies impractical in many cases. Moreover, archival tissue samples from a prostatectomy specimen may not accurately represent the current state of the tumor. To overcome these limitations, liquid biopsies using plasma samples have emerged as a minimally invasive surrogate approach to obtain real-time information on the genomic tumor profile. Growing evidence confirms the excellent concordance of liquid biopsies with tissue samples, making them an attractive alternative to traditional tissue biopsies. These assays can provide predictive and prognostic information that may enhance patient discussions and influence treatment decisions. This review focuses on the evolution and utility of circulating tumor-derived DNA (ctDNA) liquid biopsy assays in metastatic prostate cancer.